SEED-BORNE INFECTION AND WHITEFLY (Bemisia tabaci) VECTOR INTERACTION IN YELLOW MOSAIC DISEASE IN BLACK GRAM (Journal of Plant Disease Sciences, 2025)
Black gram (Vigna mungo L. Hepper) is an important pulse crop in India as well as in South East Asia. The main reason for fluctuations in average yield is various biotic stresses, which result in 5–100% yield loss. Among these, Yellow Mosaic Disease (YMD), caused by Mungbean Yellow Mosaic Virus (MYMV), is the most destructive disease of black gram in South East Asia. This disease is transmitted by whitefly (Bemisia tabaci Gennadius) and not by mechanical inoculation or seed. The main objective of the study was to identify the vectors involved in the transmission. The virus was transmitted by whitefly in a persistent manner. Virus-vector relationship revealed that a minimum of five whitefly adults with an acquisition access period of one month and an inoculation access period of five minutes were sufficient to transmit the yellow mosaic disease. The study indicated that the degenerate primers used in the present investigation amplified an approximately 900 bp amplicon of the virus. The percentage detection of the virus from the seed coat, cotyledon, embryo, and whole seed was 100%, indicating the presence of the virus in all tested samples.
Keywords: Black gram; Seed Borne; Transmission; Yellow Mosaic